An energy efficient management scheme for wireless sensor networks. (2015) - Asim, Muhammad; Mokhtar, Hala; Khan, Muhammad Zahid
Since nodes in a sensor network have limited energy, prolonging the network life time and improve its scalability become important. Hierarchical clustering models are known to be a promising solution to tackle scalability issues in an energy efficient way. However, existing hierarchical clustering schemes offer various limitations. For example, existing clustering schemes consume large amounts of energy in cluster formation and re-formation. To address this issue, we present a cellular architecture to create a control hierarchical structure for wireless sensor networks. In the proposed architecture, nodes cooperate to form clusters by grouping cells at each level of network hierarchy, ensuring maximal energy coverage and minimal energy expenditure with relatively uniform distribution of load within the network. We evaluate the performance by simulation. The results obtained from the simulation show that our clustering architecture is more energy efficient and achieves better energy consumption distribution than existing methods.